Effect Of Environmental Conditions On Energy Efficiency Of Aac-Based Building Envelopes - V. Koci; J. Madera; R. Cerny (Zenodo, 2012)
Calculations of energy efficiency of several AACbased building envelopes under different climatic conditions are presented. As thermal insulating materials, expanded polystyrene and hydrophobic and hydrophilic mineral wools are assumed. The computations are accomplished using computer code HEMOT developed at Department of Materials Engineering, Faculty of Civil Engineering at the Czech Technical University in Prague. The climatic data of Athens, Kazan, Oslo, Prague and Reykjavík are obtained using METEONORM software. : {"references": ["D. Chwieduk, Towards, \"Sustainable-energy buildings,\" Applied\nEnergy, vol. 76, no. 1-3, pp. 211-217, 2003", "EuroACE, Towards Energy Efficient Buildings in Europe, final report\nJune (ec.europa.eu), 2004.", "I.B. Topcu, T. Uygunoglu, \"Properties of autoclaved lightweight\naggregate concrete,\" Building and Environment, vol. 42, no. 12, Indoor\nAir 2005 Conference, pp. 4108-4116, 2007.", "M. Jerman,V. Ko\u2500\u00ec\u251c\u00a1, J. Mad\u2500\u00f8ra, J. V\u251c\u00a2born\u251c\u00a2, R. \u2500\u00eeern\u251c\u00a2, \"Water and heat\ntransport parameters of materials involved in AAC-based building\nenvelopes,\" in 1st Central European Symposium on Building Physics.\nLodz: Technical University of Lodz, 2010, pp. 39-45", "X.C. Qiao, B.R. Ng, M. Tyrer, C.S. Poon, C.R. Cheeseman, \"Production\nof lightweight concrete using incinerator bottom ash,\" Construction and\nBuilding Materials, vol. 4, pp. 473-480, 2008.", "H. Kurama, I.B. Topcu, C. Karakurt, \"Properties of the autoclaved\naerated concrete produced from coal bottom ash,\" Journal of Materials\nProcessing Technology, vol. 2, pp. 767-773, 2009.", "W. Wongkeo, A. Chaipanich, \"Compressive strength, microstructure and\nthermal analysis of autoclaved and air cured structural lightweight\nconcrete made with coal bottom ash and silica fume,\" Materials Science\nand Engineering, vol. 16-17, pp. 3676-3684, 2010.", "E. Holt, P. Raivio, \"Use of gasification residues in aerated autoclaved\nconcrete\", Cement and Concrete Research vol. 4, pp. 796-802, 2005.", "M.S. Goual, A. Bali, F. de Barquin, R.M. Dheilly, M. Queneudec,\n\"Isothermal moisture properties of Clayey Cellular Concretes elaborated\nfrom clayey waste, cement and aluminium powder,\" Cement and\nConcrete Research, vol. 9, pp. 1768-1776, 2006.\n[10] A. Hauser, U. Eggenberger, T. Mumenthaler, \"Fly ash from cellulose\nindustry as secondary raw material in autoclaved aerated concrete,\"\nCement and Concrete Research, vol. 3, pp. 297-302, 2009.\n[11] CSN 73 0540-2 Thermal protection of buildings - part 2: Requirements,\nCzech Office for Standards, Metrology and Testing, Prague, 2007\n[12] Approved Document L1A: Conservation of Fuel and Power in New\nDwellings, London: RIBA Enterprises, 2010.\n[13] H.M. Kuenzel, Simultaneous Heat and Moisture Transport in Building\nComponents, Ph. D. Thesis. IRB Verlag, Stuttgart, 1995.\n[14] R. \u010cern\u00db, Complex System of Methods for Directed Design and\nAssessment of Functional Properties of Building Materials: Assessment\nand Synthesis of Analytical Data and Construction of the System, CTU\nPrague, 2010.\n[15] J. Kruis, T. Koudelka, T. Krej\u2500\u00ec\u251c\u00a1, \"Efficient computer implementation of\ncoupled hydro-thermo-mechanical analysis,\" Mathematics and\nComputers in Simulation, vol. 80, pp. 1578-1588, 2010.\n[16] Grunewald, J. DELPHIN 4.1 - Documentation, Theoretical\nFundamentals, TU Dresden, Dresden. 2000.\n[17] M. Ji\u0159i\u2500\u00eckov\u251c\u00ed, R. \u2500\u00eeern\u251c\u00a2, \"Effect of Hydrophilic Admixtures on Moisture\nand Heat Transport and Storage Parameters of Mineral Wool,\"\nConstruction and Building Materials, vol. 20, pp. 425-434, 2006.\n[18] M. Jerman, J. Mad\u2500\u00f8ra, R. \u2500\u00eeern\u251c\u00a2, \"Computational Modeling of Heat and\nMoisture Transport in a Building Envelope with Hydrophilic Mineral\nWool Insulation, in Proc. of the 8th Symposium on Building Physics in\nthe Nordic Countries. Lyngby: Technical University of Denmark,\nBYG.DTU, pp. 449-456, 2008.\n[19] V. Ko\u010d\u00ed, J. V\u00dbborn\u00db, R. \u010cern\u00db, \"Computational and Experimental\nCharacterization of Building Envelopes Based on Autoclaved Aerated\nConcrete,\" Materials Characterization V Computational Methods and\nExperiments, A.A. Mammoli, C.A. Brebbia, A. Klemm (eds.).\nSouthampton: WIT Press, 2011, pp. 363-373."]}